A Review of Rod Ellis’s Contributions to Second Language Acquisition and Language Teaching - Ismail, Nyak Mutia; Fitria, Nora (Jurnal Sociohumaniora Kodepena (JSK), 2024)
Rod Ellis’s contributions to second language acquisition (SLA) and language teaching have been transformative, offering a comprehensive understanding of how languages are learned and taught. This paper explores his major theoretical frameworks, including Task-Based Language Teaching (TBLT), the Focus on Form approach, and his work on interlanguage development. Ellis’s emphasis on balancing communicative competence with linguistic accuracy has shaped modern teaching methodologies, providing educators with practical strategies for effective classroom instruction. The discussion highlights Ellis’s impact on curriculum design, teacher training, and assessment practices, emphasizing his role in bridging the gap between SLA theory and practical application. His research on feedback, task complexity, and individual learner differences continues to inform contemporary studies and teaching practices, demonstrating the enduring relevance of his work. As the field of language education evolves, Ellis’s frameworks remain adaptable to emerging trends, including the integration of technology and the increasing demand for multilingual competence. His insights provide a foundation for innovation, guiding the development of AI-powered tools and virtual learning environments. This study underscores Ellis’s lasting influence on SLA and language teaching, emphasizing the need for continued exploration of his work to address future challenges and opportunities in global language education.